2022
DOI: 10.1002/hpm.3443
|View full text |Cite
|
Sign up to set email alerts
|

Towards a national strategy for the provision of spiritual care during major health disasters: A qualitative study

Abstract: Background: Spirituality is beneficial to health. Evidence around the benefits of Spiritual care (SC) is advancing, and training is becoming part of healthcare professional development. As the COVID-19 crisis showed, during major health disasters (MHDs), the demand for SC grows exponentially, while the burden of care and focus on preserving life often hamper its provision. Nonetheless, existing health emergency strategic frameworks lack preparedness for the provision of SC. Aim: The aim of this study was to id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Similarly to rituals and death rituals, spiritual care is characterised by the central role of the body, as within the broader religion/spirituality field, spiritual care has also a prominent healing purpose. This particular caring goal of spirituality makes it more problematic to 'go live', as literature is suggesting, including this as well as another study we have conducted with health and social care professionals (Papadopoulos et al 2021b(Papadopoulos et al , 2022. This is because, we maintain, healing and care sit within that ethical and existential dimension of not only being there, but of being-with the other (Heidegger 2019).…”
Section: The Body the Group And The Priestmentioning
confidence: 97%
“…Similarly to rituals and death rituals, spiritual care is characterised by the central role of the body, as within the broader religion/spirituality field, spiritual care has also a prominent healing purpose. This particular caring goal of spirituality makes it more problematic to 'go live', as literature is suggesting, including this as well as another study we have conducted with health and social care professionals (Papadopoulos et al 2021b(Papadopoulos et al , 2022. This is because, we maintain, healing and care sit within that ethical and existential dimension of not only being there, but of being-with the other (Heidegger 2019).…”
Section: The Body the Group And The Priestmentioning
confidence: 97%
“…Returning to the EDI findings of the two spirituality‐related studies conducted during the Covid pandemic by myself and colleagues (Papadopoulos et al, 2020, 2021), we have recommended that public health policymakers, managers, nurses and other healthcare workers including spiritual care providers must urgently collaborate to: Provide training related to major health disasters and emergencies in order to enhance health workers' knowledge and culturally competent and compassionate skills for effective and equitable care, including spiritual support; Review policies such as visiting of patients and accessible and effective protective equipment for health and spiritual providers as well as for the public; Embrace the adoption of artificial intelligent devices and robotics, making their availability equitable and their operation user friendly; Develop a comprehensive national strategy for major health disasters and emergencies, which includes the provision of culturally competent spiritual care for patients, the public and the staff. We all know that the world was caught unprepared for the arrival of the Covid pandemic. Preparing for the next major health disaster must start now.…”
mentioning
confidence: 99%
“…My presentation (Papadopoulos, 2022) addressed the spiritual care provision to hospitalized Covid-19 patients in England. The two studies I conducted with my colleagues at the Research Centre for Transcultural Studies in Health (Papadopoulos et al, 2020(Papadopoulos et al, , 2021 revealed, among many other challenges, three main issues related to equality, diversity and inclusion (EDI).…”
mentioning
confidence: 99%